(untitled) (Jurnal Bahasa, 2024)
Didacticism is the main characteristic of children’s literature. Since the earliest tradition of oral storytelling, children’s stories have been used to convey lessons, particularly concerning moral values that align with societal norms. These stories are conveyed in a manner that is comprehensible and suitable with the children’s level of knowledge and developing cognitive abilities. Thus, it is important to consider such factors when children’s stories are translated from a foreign to target language. Elements that are too foreign or unfamiliar may affect children’s interest and understanding. Although source-oriented translation strategy has its own strengths and benefits, several scholars of translation and children’s literature believe that target-oriented translation strategy can produce translations that are more familiar for children readers. Therefore, this study examines the translation of culture-specific items (CSI) in Enid Blyton’s short stories based on the classification of translation methods by Newmark (1988). The findings showed that translators of Blyton’s short stories employed a target-oriented strategy to translate the stories into Malay language. Among the most frequently used translation procedures are adaptation and deletion. Through a target-oriented translation strategy, the produced translations depict stories that are set in local context and conform to the norms of Malay Muslim society. Keywords: Translation strategies, translation procedures, children’s literature, English-Malay translation, Enid Blyton, elements of culture Full text: PDF